2002
DOI: 10.1046/j.0022-3042.2001.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of carnosine‐Cu(II) complexes prevents and reverts the inhibitory action of copper in P2X4 and P2X7 receptors

Abstract: To further analyze the action of copper on brain synaptic mechanisms, the brain dipeptide carnosine (b-alanyl-L-histidine) was tested in Xenopus laevis oocytes expressing the rat P2X 4 or P2X 7 receptors. Ten micromolar copper halved the currents evoked by ATP in both receptors; co-application of carnosine plus copper prevented the metal induced-inhibition with a median effective concentration of 12.1 3.9 and 12.0 5.5 lM for P2X 4 and P2X 7 , respectively. Zinc potentiated only the P2X 4 ATP-evoked currents; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Copper and zinc also modulate other members of the P2X family of receptors, but their effects depend on the receptor subtype. For example, both zinc and copper facilitate the ATP-evoked responses on the P2X 2 receptor (14,15) whereas in the P2X 7 receptor, copper inhibits the ATP-gated currents, whereas zinc is virtually without effect (13). These findings further support the notion that the P2X purinoceptors may have separate metal-binding sites to modulate the channel activity.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Copper and zinc also modulate other members of the P2X family of receptors, but their effects depend on the receptor subtype. For example, both zinc and copper facilitate the ATP-evoked responses on the P2X 2 receptor (14,15) whereas in the P2X 7 receptor, copper inhibits the ATP-gated currents, whereas zinc is virtually without effect (13). These findings further support the notion that the P2X purinoceptors may have separate metal-binding sites to modulate the channel activity.…”
supporting
confidence: 75%
“…Acuñ a-Castillo et al (12) and Coddou et al (13) reported that zinc potentiates the ATP-evoked currents whereas copper has an inhibitory effect on the activity of this receptor. Based on these findings, Acuñ aCastillo et al (12) proposed that trace metals modulate the activity of the P2X 4 receptor via two separate metal-binding sites.…”
mentioning
confidence: 99%
“…These functional characteristics of ATP-evoked currents are compatible with the activation of P2X4R and/or of P2X7R, but not of P2X1R (Coddou et al, 2002). To have an estimation of the pharmacological profile of these microglia P2XRs, we then analyzed the effect of two agonists and eight antagonists on the response evoked by repetitive applications of 500 M ATP in free [Ca 2ϩ , Mg 2ϩ ] out (see Materials and Methods).…”
Section: Atp Evokes Biphasic Membrane Currents In Embryonic Microgliamentioning
confidence: 99%
“…We then tested the effect of Cu 2ϩ and Zn 2ϩ on ATP-evoked currents. Cu 2ϩ inhibits both P2X7Rs and P2X4Rs whereas Zn 2ϩ increases the activity of P2X4R and is virtually without effect on rat P2X7R expressed in oocytes (Coddou et al, 2002) or fully blocks the activity of these two receptors expressed in transfected human embryonic kidney (HEK) cells (Liu et al, 2008). Then 50 M Cu 2ϩ evoked a significant ( p Ͻ 0.01) Ϸ77% inhibition (Fig.…”
Section: Atp Evokes Biphasic Membrane Currents In Embryonic Microgliamentioning
confidence: 99%
See 1 more Smart Citation